A companion to postcolonial studies - Schwarz, Henry; Ray, Sangeeta (Blackwell companions in cultural studies, 2005)
This volume examines the tumultuous changes that have occurred and are still occurring in the aftermath of European colonization of the globe from 1492 to 1947. Ranging widely over the major themes, regions, theories and practices of postcolonial study today, the volume presents original essays by the leading proponents of postcolonial study in the Americas, Europe, India, Africa, East and West Asia. Their contributions provide clear introductions to the major social and political movements underlying colonization and decolonization, accessible histories of the literature and culture, separate regions affected by European colonization, and introductory essays on the major thinkers and intellectual schools that have informed strategies of national liberation worldwide. This volume is unique in providing an incisive summary of the long history and theory of modern European colonization in local detail and global scale. It will be a necessary reference tool for years to come.